Analisis Biaya Diferensial dan Variable Costing dalam Pengambilan Keputusan Pesanan Khusus pada UMKM Batik Jumantara - Zanah, Umi Roikhatul; Solikah, Mar’atus; Zaman, Badrus (FEB Universitas Maritim Semarang, 2025)
This study aims to analyze the application of differential costing and variable costing methods in making special order decisions at Batik Jumantara MSMEs. The method used is quantitative descriptive with a case study approach in the period 2024. The results of the study indicate that the differential costing approach is able to provide more accurate information on the evaluation of the benefits of special orders. By using the variable costing method, companies can separate fixed and variable costs, so that business decisions can be taken more effectively. These findings contribute to strengthening the managerial accounting system of MSMEs and increasing business efficiency and profitability.